تأثير ترجمة الأسماء المركبة من معجم اللغة الإندونيسية الكبير على لغة متعلمي اللغة العربية - Refa Fitriani; Meitha Kartika Herdiyanti (Rayah Al-Islam, 2019)
This study focused on translating the correct compound words into Arabic that become a problem from the Arabic learners as they translate these words into literal translation. The way in which this study was carried out was based on the scientific approach: the descriptive analytical approach for the analysis of the correct translation of the compound words, the method of testing and resolution to learn the effect of translating compound words on Arabic learners and the resolution was composed of nine axes. This study has shown a number of results, the most important of which are: compound words are a set of two or more words that have the same meaning, analysis of the correct translation of the compound words from (KBBI) into three sections, namely: Compound words that were Contrary to the composition of the Arabic vocabulary, of compound words in the type of conventional expression compound words that correspond to the composition of the Arabic vocabulary, and The field study found that the correct translation of the compound words increases the terminology and vocabulary of students to develop the competency level of their language, The correct translation of compound words gives positive effect for development of Arabic learners.